Una aproximació pragmàtica als llibres proverbials catalans - Conca, Maria (Caplletra. Revista Internacional de Filologia, 2015)
Conca studies some catalan Proverbs from Middle Ages in a semiotic and pragmatic scope. Her paper deals with the borders between literary and non literary discourse in the field of this genre: proverbs as isolated, decontextualized texts that goin to the accumulative thesaurus of the national culture.